2022
DOI: 10.1186/s12876-022-02582-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic clinical indexes for prediction of acute gangrenous cholecystitis and acute purulent cholecystitis

Abstract: Background Preoperative prediction of severe cholecystitis (SC), including acute gangrenous cholecystitis (AGC) and acute purulent cholecystitis (APC), as opposed to acute exacerbation of chronic cholecystitis (ACC), is of great significance, as SC is associated with high mortality rate. Methods In this study, we retrospectively investigated medical records of 114 cholecystitis patients, treated in Shanghai No. 6 People’s Hospital from February 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…During disease progression, these cells undergo significant metabolic rewiring to adapt to their high energy demands and changing environmental conditions [ 22 ]. Recent research has confirmed that changes in patients’ metabolic indices (including BMI, low-density lipoprotein, and total cholesterol) are associated with the prognoses of patients with acute cholecystitis [ 23 ]. Assessing body composition parameters, such as fat and muscle tissue, can be used to assess a patient’s energy reserves and expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…During disease progression, these cells undergo significant metabolic rewiring to adapt to their high energy demands and changing environmental conditions [ 22 ]. Recent research has confirmed that changes in patients’ metabolic indices (including BMI, low-density lipoprotein, and total cholesterol) are associated with the prognoses of patients with acute cholecystitis [ 23 ]. Assessing body composition parameters, such as fat and muscle tissue, can be used to assess a patient’s energy reserves and expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have elucidated that white blood cell (WBC) count and leukocyte subtype cells are valuable indicators for predicting the inflammatory process in acute cholecystitis. [13][14][15][16][17] WBC count has been established as the primary biomarker for assessing the severity of cholecystitis. 4 Elevated WBC count is often observed due to the robust inflammatory response triggered by gallstone blockage.…”
Section: Introductionmentioning
confidence: 99%